Instalasi Perangkat Pembangkit Listrik Tenaga Surya (PLTS) Sebagai Sumber Energi Pada Taman Gedung Makhtab Kampus Panca Budi - Chandra Danova Siringo Ringo (Pusat Riset dan Inovasi Nasional, 2022)
Electricity is a very important need for the life of many people. Especially with the increasing number of tools that use electricity as a source of energy in this day and age. With the increasing demand for electricity, the more electrical energy that must be issued, especially by PLN. Electricity is also a source of energy that is needed in all activities related to electronics, therefore its use varies greatly. The purpose of making this final project entitled